2009
DOI: 10.1021/nl8036323
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline-Amorphous Core−Shell Silicon Nanowires for High Capacity and High Current Battery Electrodes

Abstract: Silicon is an attractive alloy-type anode material for lithium ion batteries because of its highest known capacity (4200 mAh/g). However silicon's large volume change upon lithium insertion and extraction, which causes pulverization and capacity fading, has limited its applications. Designing nanoscale hierarchical structures is a novel approach to address the issues associated with the large volume changes. In this letter, we introduce a core-shell design of silicon nanowires for highpower and long-life lithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
764
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,135 publications
(803 citation statements)
references
References 43 publications
21
764
1
3
Order By: Relevance
“…Our previous EPS studies 44,45 on VLS SiNWs found that lithiation of the crystalline SiNW occurs at 0.125 V vs Li/Li ϩ , whereas lithiation of amorphous Si occurs at higher potentials (ϳ0.22 V vs Li/Li ϩ ). During the first lithiation step, a small peak at about 0.6 V is observed from initiation of the SEI formation 29 due to the reduction of the electrolyte.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous EPS studies 44,45 on VLS SiNWs found that lithiation of the crystalline SiNW occurs at 0.125 V vs Li/Li ϩ , whereas lithiation of amorphous Si occurs at higher potentials (ϳ0.22 V vs Li/Li ϩ ). During the first lithiation step, a small peak at about 0.6 V is observed from initiation of the SEI formation 29 due to the reduction of the electrolyte.…”
Section: Resultsmentioning
confidence: 98%
“…This shell is composed of polyphenylsilanes that form as a reaction byproduct during the large-scale SFLS growth of SiNWs (Ͼ10 mg). 15 Carbon coating 21 of battery materials has been frequently used to improve the electron flux to the surface of the Li insertion material, aid electron transport between particles, and to improve rate performance. For Si, carbon coating may also be used to buffer the large volume changes and control the solid electrolyte interphase (SEI) formation, as well as improve the electronic conductivity of the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The long-range disorder of amorphous materials generally makes them unable to form 1D nanostructures, which have obvious anisotropy, without any attached host [62] or particular guiding technique [63][64][65][66][67]. Nanotubes, NWs, and nanofibers are three typical types of 1D nanomaterials.…”
Section: Nanotubes Nanowires and Nanofibersmentioning
confidence: 99%
“…It is worth noting that the graphene-sulfur composite could be coupled with silicon based anode materials for rechargeable batteries with significantly higher energy density than currently possible. [31][32][33] In such batteries, Li + could be preloaded into either sulfur or silicon. 11,33 In summary, we have developed a graphene-sulfur composite material by synthesizing submicron sulfur particles coated with PEG containing surfactants and graphene sheets.…”
mentioning
confidence: 99%